ITS‐G5 performance improvement and evaluation for vulnerable road user safety services. Issue 3 (14th March 2017) - Jutila, Mirjami; Scholliers, Johan; Valta, Mikko; Kujanpää, Kaisa
Abstract : Cooperative intelligent transportation system (C‐ITS) allows to improve safety of vehicles through communications between vehicles and infrastructure. C‐ITS may also improve the safety of vulnerable road users (VRUs), but work on this issue is still in an early stage. ITS‐G5 (IEEE 802.11p), the main technology for vehicle‐to‐vehicle time‐critical communications, allows to deliver safety information over a rather long range with low latency, but obstacles in the link path and a large amount of vehicles sending at the same time may reduce performance. In this study, the authors assess and optimise the performance of ITS‐G5 for time‐critical safety conflict scenarios between vehicles and VRUs. The authors have tested various non‐line‐of‐sight (NLOS) scenarios in urban environments and line‐of‐sight (LOS) simulations to support C‐ITS message prioritisation and scalability with different amount of vehicles. Example use cases with NLOS include pedestrians crossing streets from behind objects, and low‐visibility scenarios, e.g. when VRU is behind a vehicle, behind a queue of vehicles, between vehicles, behind trees/bushes or behind a building. The LOS simulations utilise fuzzy weighted queueing mechanism for congestion control to overcome the packet losses and for data prioritisation. Based on these results, the applicability of ITS‐G5 for VRU applications is assessed and performance improved.